Effect of Feed Restriction in Period on broiler chicken Performance and Carcass traits - faraj, Hersh A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The feed restriction program is one of the main techniques in growth curve manipulation for increasing production efficiency in broiler chicken, therefore, this experiment was conducted to determine the effects of different feed restriction levels, at finisher phase from 30 to 42 days, on productive performance and carcass traits. In this experiment a number of 90 Male Ross broilers were used, the chicks were distributed into five treatments at three replications for each treatment and six chicks for each replication. The first group was control (T1) which the chicks of this group were fed according to Ross Management Manual, and (10, 15, 20 and 25% less than Ad-libitum) for T2, T3, T4 and T5 respectively. The results showed that feed intake at different levels was significantly (p<0.05) less than the control group. Meanwhile, at 42 days old Live weight, body weight gain and feed conversion ratio of (T2, T3, T4 and T5) were numerically less than the control group, nevertheless, these differences were not significant (p>0.05). The results also show that carcass traits were significantly (p<0.05) affected by feed restriction at which abdominal fat percentage in all treatment groups were significantly (p>0.05) lower compared to control group. Meanwhile carcass weight, gizzard percentage and dressing percentage in all treatments were numerically lower than the control groups, however differences were not significant (p>0.05). In conclusion; results shows that using feed restriction (less than the Ad-libitum feed intake decreased significantly the feed intake without any effect on productive performance and carcass traits.
Keywords: Performance; Carcass traits; Feed Restriction; Finisher Period; Broiler